Modified unipolar carrier-based PWM strategy for three-level neutral-point-clamped voltage source inverters - Watcharin Srirattanawichaikul (2018)
This paper presents a simple modified unipolar carrier-based pulsewidth modulation (CBPWM) strategy for the three-level neutral-point-clamped (NPC) voltage source inverter (VSI). Analytical expressions for the relationship between modulation reference signals and output voltages are derived. The proposed modulation technique for the three-level NPC VSI includes the maximum and minimum of the three-phase sinusoidal reference voltages with zero-sequence voltage injection concept. The proposed modified CB-PWM strategy incorporates a novel method that requires only of one triangular carrier wave for generate the gating pulses in three-level NPC VSI. It has the advantages of being simplifying the algorithm with no need of complex two/multi-carrier pulsewidth modulation or space vector modulation (SVM) and it's also simple to implement. The possibility of the proposed CB-PWM technique has been verified though computer simulation and experimental results.